2013
DOI: 10.1074/jbc.m113.479253
|View full text |Cite
|
Sign up to set email alerts
|

Hsp110 Is a Bona Fide Chaperone Using ATP to Unfold Stable Misfolded Polypeptides and Reciprocally Collaborate with Hsp70 to Solubilize Protein Aggregates

Abstract: Background: Hsp110s are considered as mere nucleotide exchange factors of the Hsp70s. Results: Human cytosolic Hsp110s can use ATP to unfold misfolded polypeptides and act as equal partner with Hsp70 to solubilize stable protein aggregates. Conclusion: Hsp110s are Hsp70-like polypeptide unfolding chaperones. Significance: Hsp110s are powerful disaggregating chaperones that can collaborate with Hsp70s to detoxify misfolding proteins in degenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(180 citation statements)
references
References 60 publications
3
172
3
2
Order By: Relevance
“…7C). In accordance with this, we also observed the up-regulation of the chaperone Hsp110 (HSPH1) that has recently been described as part of the cytosolic machinery responsible for the disaggregation of peptide aggregates (55)(56)(57). The other two main elements of the disaggregating complex, Hsp40 (DNAJA1) and Hsp70 (HSPA1A), were also up-regulated in cells incubated with PepL (Fig.…”
Section: Pepl But Not Peps Internalization Requires Hsp70 and Issupporting
confidence: 69%
“…7C). In accordance with this, we also observed the up-regulation of the chaperone Hsp110 (HSPH1) that has recently been described as part of the cytosolic machinery responsible for the disaggregation of peptide aggregates (55)(56)(57). The other two main elements of the disaggregating complex, Hsp40 (DNAJA1) and Hsp70 (HSPA1A), were also up-regulated in cells incubated with PepL (Fig.…”
Section: Pepl But Not Peps Internalization Requires Hsp70 and Issupporting
confidence: 69%
“…12 In recent years, HSP110 has become a new point of interest in the field of HSP and cancer, mainly thanks to its excellent chaperoning capacity of peptide antigens, which makes it a powerful tool for vaccine development. 48,49 Until our recently published works demonstrating the essential role of HSP110 in CRC, its role in tumor development remained almost unexplored. This study brings new information to the emerging role of extracellular HSP110 in the inhibition of the immune system in the context of tumor microenvironment.…”
Section: E1170264-6mentioning
confidence: 99%
“…However, Hsp105 had the intrinsic ability to bind ATP-FAM and hydrolyze ATP (Fig. 6D) (80), so its ability to promote nucleotide release could not be reliably tested. Finally, when we combined Hsp105 with Hsp72 and the four J proteins, we found that it was unable to significantly promote nucleotide hydrolysis of any of the Hsp72 combinations ( Fig.…”
Section: Hsp105 Competes With Bag Proteins and Acts As A Nef-mentioning
confidence: 99%